Porous coordination polymer as well as preparation method and application thereof

By purifying and nitroizing the waste PEN plastic, a porous coordination polymer with an internal helical structure was prepared, which solved the problems of low purity and poor quality of the product during the conversion of waste plastics in the prior art, and achieved a porous coordination polymer with high physical and chemical stability and catalytic performance.

CN120082047APending Publication Date: 2025-06-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311639002.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-01
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

When the prior art converts waste plastic into porous coordination polymers, there are problems such as pyrolysis methods that lead to PET chain breakage and insufficient decomposition, resulting in low purity and poor quality of subsequent products.

Method used

By synchronizing the ligand purification and nitrolation of various methods such as treating waste PEN plastic and reflux of acid liquid, a porous coordination polymer with an internal helical structure was prepared, and a porous coordination polymer with excellent physical and chemical stability and catalytic performance was formed.

Benefits of technology

The porous coordination polymer has achieved high thermal stability, high crystallization purity, large specific surface area and excellent catalytic performance, and solved the problems of low purity and poor quality of the product in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120082047A_ABST
    Figure CN120082047A_ABST
Patent Text Reader

Abstract

The invention discloses a porous coordination polymer as well as a preparation method and application thereof. The porous coordination polymer takes metal gallium as a central ion and a structure containing a nitro functional group as a ligand; the molecular formula of the porous coordination polymer is [C12H4N2O8Ga2] n, wherein n ranges from 150 to 350. The porous coordination polymer provided by the invention has the advantages of high thermal stability, high crystal purity, large specific surface area, excellent catalytic performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of resource utilization of solid waste, and particularly relates to a porous coordination polymer, a preparation method thereof and an application thereof. Background Art

[0002] Polyethylene naphthalate (PEN) is an important component of polyester plastics. It is usually formed by the polycondensation reaction of 2,6-naphthalenedicarboxylic acid (NDA) and ethylene glycol, and is an excellent engineering plastic raw material. The chemical structure of PEN is similar to that of polyethylene terephthalate (PET), but the difference is that the benzene ring in PET is replaced by a naphthalene ring with better symmetrical stability in its molecular chain. Therefore, PEN has higher chemical stability, physical hardness and mechanical strength, as well as good radiation resistance compared to PET. However, over time, more and more waste plastics (including PEN, PET, etc.) will enter the natural environment along with human production and life. Since it is difficult to degrade naturally, it will pose a serious threat to the earth's environment and ecology for a long time, and at the same time have an adverse impact on the human living environment and economic development.

[0003] Porous coordination polymers are a class of highly crystalline porous polymers obtained by the complex coordination reaction of metal center ions or clusters with organic acid ligands. Obtaining organic acid ligands by chemically converting waste plastics and then obtaining porous coordination polymers through specific coordination reactions is one of the reliable ways to efficiently recycle waste plastics. However, for a long time, the focus of people's attention has been on the conversion of PET plastics, and there is little research on PEN with higher added value. Therefore, it is necessary to conduct in-depth research on the conversion of PEN plastics to prepare porous coordination polymers.

[0004] CN116622085A discloses a metal-organic framework material prepared based on waste PET, a preparation method thereof and an application thereof. This method is to add a metal salt to DMF and deionized water, stir until completely dissolved to obtain a mixed solution, transfer the mixed solution to a reaction kettle, add PET powder, mix evenly and then transfer it to an oven, heat it, wash the obtained product with DMF, centrifuge it, retain the precipitate, wash the precipitate with absolute ethanol, centrifuge to obtain the product, and dry the product to obtain the metal-organic framework material. This method is simple to operate. However, only relying on the pyrolysis method to hydrolyze PET easily causes its chain breakage and incomplete decomposition, resulting in low purity of terephthalic acid obtained subsequently and poor quality of the simultaneously coordinated metal-organic framework material.

[0005] CN110283353A discloses a method for preparing metal-organic framework materials by one-step degradation of waste polyester plastics induced by polyoxometalates. This method involves adding the precursor substance of polyoxometalates to a sodium acetate buffer solution, mixing and stirring until a clear solution is obtained, then adding waste polyester plastic fragments, stirring evenly, heating to 170°C - 190°C and maintaining for 60h - 80h. After that, it is cooled, filtered, washed and dried to obtain polyoxometalate-based metal-organic framework materials. This method has the characteristics of simple process and convenient operation. However, during the hydrolysis process of polyester plastics, it is not sufficient, and the hydrolysis intermediate products will participate in the coordination reaction of the synthesis of metal-organic framework materials together with the final products, resulting in a decrease in the purity of the obtained metal-organic framework materials, that is, insufficient thermal stability and chemical stability. Summary of the Invention

[0006] In order to overcome the deficiencies of the prior art, the present invention provides a porous coordination polymer and its preparation method and application. The porous coordination polymer provided by the present invention has advantages such as high thermal stability, high crystallization purity, large specific surface area and excellent catalytic performance.

[0007] The first aspect of the present invention provides a porous coordination polymer, wherein,

[0008] The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , and the monomer of its structural formula is as follows:

[0009]

[0010] wherein, n is 150 - 350.

[0011] Further, the mass content of gallium in the porous coordination polymer is 3% - 6%.

[0012] Further, in the porous coordination polymer, the mass content of carbon is 53% - 62%, the mass content of oxygen is 21% - 33%, and the mass content of nitrogen is 2.3% - 3.7%.

[0013] Further, the porous coordination polymer has an inner helical structure.

[0014] Further, the specific surface area of the porous coordination polymer is 1280m 2 / g - 1460m 2 / g, the microporosity is 75% - 85%, and the average pore diameter is 0.68nm - 0.85nm.

[0015] ​Furthermore, the total acid amount of the porous coordination polymer is 1.35 mmol / g to 1.56 mmol / g, the medium-strong acid amount is 0.63 mmol / g to 0.75 mmol / g, and the ratio of the L acid amount to the B acid amount (L / B) is 1.31 to 1.42.

[0016] The second aspect of the present invention provides a preparation method of the above-mentioned porous coordination polymer, comprising the following steps:

[0017] (1) Synthesize the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid;

[0018] (2) Dissolve the gallium salt in a mixed solvent, add the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid described in step (1), and react to obtain the porous coordination polymer.

[0019] Furthermore, the chemical structural formula of the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid is as follows:

[0020]

[0021] Furthermore, the synthesis method of the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid in step (1) can obtain the ligand by nitrating 2,6-naphthalenedicarboxylic acid. Preferably, 2,6-naphthalenedicarboxylic acid is first purified from waste PEN plastic, and then the ligand is obtained by nitrating 2,6-naphthalenedicarboxylic acid. This preferred method can realize the reuse of waste PEN plastic, reduce the cost of preparing the porous coordination polymer, and synchronously realize ligand purification and ligand nitration through various methods such as treating PEN plastic, nitration, and acid solution reflux, which not only ensures high purity of the obtained 4,8-dinitroterephthalic acid, but also effectively inhibits the alkyl transfer reaction of the nitro functional group to generate other isomers.

[0022] Furthermore, the method for synthesizing the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid in step (1) specifically comprises the following steps:

[0023] (i) Take waste PEN plastic, crush it, place it in an alkali solution for a first reaction, and then add an acid solution for a second reaction, wash and dry to obtain 2,6-naphthalenedicarboxylic acid;

[0024] (ii) Dissolve the 2,6-naphthalenedicarboxylic acid in step (i) in acid solution A, and then gradually add it dropwise to acid solution B for nitration reaction to obtain 4,8-dinitro-2,6-naphthalenedicarboxylic acid.

[0025] Further, the waste PEN plastic described in step (i) can be repeatedly rinsed and dried before being pulverized. The drying temperature is preferably 50°C to 70°C, and the time is 6h to 12h. The particle size of the powder after pulverizing the PEN plastic is 60 mesh to 200 mesh, preferably 120 mesh to 150 mesh.

[0026] Further, the lye described in step (i) is selected from aqueous solutions of sodium hydroxide and / or potassium hydroxide, and its mass concentration is 9.5% to 25%, preferably 13% to 17%.

[0027] Further, the mass ratio of the waste PEN plastic described in step (i) to the lye is 1:(1 to 10), preferably 1:(2.7 to 5.3).

[0028] Further, after placing the waste PEN plastic in the lye in step (i), stirring is preferably carried out, with a rotation speed of 300 rpm to 500 rpm and a time of 10 min to 30 min.

[0029] Further, the first reaction described in step (i) is a static reaction, where the first reaction temperature is 150°C to 250°C, preferably 180°C to 220°C, and the time is 10h to 35h, preferably 18h to 26h.

[0030] Further, the acid solution described in step (i) is selected from one or more of aqueous oxalic acid solution, aqueous citric acid solution, and aqueous malic acid solution, preferably aqueous oxalic acid solution, and the mass concentration of the acid solution is 28% to 36%.

[0031] Further, the mass ratio of the PEN plastic described in step (i) to the acid solution is 1:(4 to 15), preferably 1:(6.8 to 11.3).

[0032] Further, the second reaction described in step (i) is a heating and stirring reaction, where the heating temperature is 60°C to 100°C, the stirring rotation speed is 300 rpm to 500 rpm, and the time is 1h to 8h.

[0033] Further, the solvent used for washing in step (i) is selected from any one of deionized water, absolute ethanol, and acetone. The drying conditions are as follows: the drying temperature is 80°C to 150°C, and the drying time is 7h to 16h.

[0034] Further, the acid solution A described in step (ii) is selected from aqueous hydrochloric acid solution, and its mass concentration is 5% to 20%, preferably 8% to 14%.

[0035] Further, the mass ratio of 2,6-naphthalenedicarboxylic acid to acid solution A in step (ii) is 1:(0.8 to 8.6), preferably 1:(1.9 to 4.2).

[0036] Further, the addition of acid solution B in step (ii) is preferably carried out under a cooling ambient temperature and stirring, where the cooling ambient temperature is -15°C to 6°C, preferably -3.5°C to 2.7°C; the stirring speed is 8000 rpm to 16000 rpm, preferably 10000 rpm to 13000 rpm, and the stirring time is 30 min to 60 min.

[0037] Further, the acid solution B in step (ii) is selected from one or more of nitroacetic acid, aqua regia, and 4-nitrocinnamic acid, preferably nitroacetic acid, and the mass concentration of the acid solution B is 13% to 25%.

[0038] Further, the mass ratio of 2,6-naphthalenedicarboxylic acid to acid solution B in step (ii) is 1:(0.25 to 2.35), preferably 1:(0.63 to 1.34).

[0039] Further, the ratio of the mass of 2,6-naphthalenedicarboxylic acid to the dropping rate of acid solution B in step (ii) is 1 g:(0.75 mL / min to 3.5 mL / min), preferably 1 g:(1.05 mL / min to 1.75 mL / min).

[0040] Further, the heating reaction in step (ii) undergoes a two-stage heating reaction. In the first stage, the solution temperature is programmed to rise to the first reaction temperature under reflux conditions and then react at a constant temperature; the first reaction temperature is 30°C to 90°C, preferably 40°C to 70°C, the heating rate is 1°C / min to 10°C / min, preferably 2.3°C / min to 3.9°C / min, and the constant temperature time is 10 min to 100 min, preferably 45 min to 80 min. In the second stage, the temperature is continuously raised to the second reaction temperature of 50°C to 160°C, preferably 70°C to 120°C, and the constant temperature time is 4 h to 20 h, preferably 7 h to 13 h, where the second reaction temperature is at least 30°C higher than the first reaction temperature.

[0041] Further, after the heating reaction in step (ii), conventional cooling, suction filtration, washing, and drying treatments in the art are carried out. The washing solvent is selected from one or more of deionized water, absolute ethanol, and acetone, preferably acetone. The drying temperature is 50°C to 100°C, and the time is 16 h to 30 h.

[0042] Further, in step (2), the gallium salt is selected from one or more of gallium nitrate nonahydrate, gallium chloride hexahydrate, and gallium sulfate, preferably gallium nitrate nonahydrate.

[0043] Further, the mixed solvent described in step (2) is at least one organic solvent selected from N,N-dimethylformamide, acetonitrile, anhydrous methanol, N,N-dimethylacetamide, and diethyl ether and water, and the mass ratio of the organic solvent is (1.4 - 2.5):(0.08 - 0.85); the mixed solvent is preferably a combination of N,N-dimethylacetamide, acetonitrile, and water, wherein the mass ratio of N,N-dimethylacetamide, acetonitrile, and water is 1:(0.4 - 1.5):(0.08 - 0.85), preferably 1:(0.8 - 1.2):(0.25 - 0.58).

[0044] Further, in step (2), before adding the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid, ultrasonic treatment can be performed first. The ultrasonic treatment power is 28 kHz - 120 kHz, preferably 35 kHz - 50 kHz, and the time is 1 min - 15 min; after adding the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid, ultrasonic treatment can also be performed. The ultrasonic treatment power is 42 kHz - 180 kHz, preferably 85 kHz - 130 kHz, and the time is 5 min - 30 min.

[0045] Further, in step (2), the mass ratio of the gallium salt, the mixed solvent, and the ligand is 1:(73 - 156):(0.21 - 0.96), preferably 1:(102 - 128):(0.31 - 0.57).

[0046] Further, in step (2), the gallium salt is dissolved in the mixed solvent, and the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid is added for reaction. The reaction is a static reaction, the reaction temperature is 55°C - 135°C, preferably 70°C - 115°C, and the time is 12 h - 36 h, preferably 20 h - 30 h.

[0047] Further, in step (2), after the reaction, conventional cooling, suction filtration, washing, and drying treatments in the art are performed. The organic solvent for washing is selected from one or more of N,N-dimethylformamide, anhydrous methanol, and diethyl ether. Preferably, it is a combination of N,N-dimethylformamide and anhydrous methanol, and the mass ratio of N,N-dimethylformamide and anhydrous methanol is 1:(0.5 - 2), preferably 1:(0.8 - 1.4); the drying is preferably vacuum drying, the temperature of the drying treatment is 100°C - 210°C, preferably 140°C - 180°C, and the time is 4 h - 18 h, preferably 9 h - 14 h.

[0048] The third aspect of the present invention provides an application of the above-mentioned porous coordination polymer in the preparation of chloropropane carbonate by the cycloaddition reaction of epichlorohydrin and carbon dioxide.

[0049] Further, in the application, a porous coordination polymer is used as a catalyst, and epichlorohydrin contacts with carbon dioxide and the catalyst to carry out a cycloaddition reaction to obtain chloropropane carbonate.

[0050] Further, in the application, an aqueous solution of tetrabutylammonium bromide is added as a reaction assistant. Among them, the mass ratio of epichlorohydrin, the aqueous solution of tetrabutylammonium bromide and the catalyst is 1:(0.65-1.17):(0.16-0.34).

[0051] Further, the mass concentration of the aqueous solution of tetrabutylammonium bromide is 7.3%-13.6%.

[0052] Further, the reaction conditions are as follows: the reaction temperature is 50°C-80°C, the reaction pressure is normal pressure, and the reaction time is 30h-60h.

[0053] Further, the carbon dioxide can be pure carbon dioxide or a mixed gas containing carbon dioxide. The mixed gas containing carbon dioxide is preferably the waste gas from a coal-fired power plant, specifically including at least CO 2 , N 2 , H 2 O, O 2 , SO 2 . Among them, the volume ratio of CO 2 in the mixed gas is 10%-20%.

[0054] Further, in the reaction, the dosages of the carbon dioxide and the catalyst are (70 mL / min-130 mL / min carbon dioxide):1 g catalyst.

[0055] Compared with the prior art, the present invention has the following advantages:

[0056] (1) The porous coordination polymer provided by the present invention uses gallium metal as the central ion and a ligand containing a nitro functional group structure. The two are complexed to have an inner helical structure. Due to the spatial extensibility and symmetry, the porous coordination polymer has high physical and chemical stability. Moreover, the ligand adopted in the present invention is nitrated at the 4th and 8th positions of the ligand on 2,6-naphthalenedicarboxylic acid to obtain a nitro functional group. In the process of further enhancing the acid and water resistance stability of the porous coordination polymer, the number of L acid centers of the porous coordination polymer is also enriched, that is, the nucleophilic halogenation reaction performance of the porous coordination polymer with epoxyhaloalkanes is enhanced, the reaction energy barrier is reduced, and the raw material conversion rate is improved. In addition, the nitro functional groups at the 4th and 8th positions of the ligand increase the steric hindrance performance in the stage of the target product converting to isomers. Therefore, the reaction process has high selectivity and target product yield.

[0057] (2) In the method for preparing the ligand of the present invention, various methods such as treating PEN plastic and refluxing with acid solution are used to simultaneously achieve ligand purification and ligand nitration. This not only ensures high purity of the obtained 4,8-dinitrophthalic acid, but also effectively inhibits the alkyl transfer reaction of the nitro functional group to generate other isomers.

[0058] (3) In the method for preparing the porous coordination polymer of the present invention, the ligand reacts with a gallium salt to form an inner helical structure. Moreover, the method of the present invention realizes an effective conversion from a waste plastic to a new type of plastic, providing a new solution for alleviating waste plastic pollution. The method of the present invention has a simple process, is economical and environmentally friendly, is easy to promote, and has broad application prospects in industrial production. Description of the Drawings

[0059] Figure 1 Scanning electron micrograph (SEM) of the porous coordination polymer prepared in Example 1;

[0060] Figure 2 Scanning electron micrograph (SEM) of the porous coordination polymer prepared in Comparative Example 5. Detailed Embodiments

[0061] The following examples are used to further illustrate the porous coordination polymer of the present invention, its preparation method and application. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation manners and specific operation processes are given. However, the protection scope of the present invention is not limited to the following examples.

[0062] In the following examples, the experimental methods, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all purchased from conventional biochemical reagent stores.

[0063] In the present invention, a HITACHI 3-4800 type field emission scanning electron microscope of Hitachi, Japan is used to observe the crystal grain size and morphological characteristics of the porous coordination polymer. The types and contents of elements in the porous coordination polymer are qualitatively and quantitatively analyzed by an energy spectrometer (Oxford Instruments, UK) connected to the scanning electron microscope.

[0064] In the present invention, the Materials Studio 7.0 software is used to calculate the spatial structure layout of the porous coordination polymer and the reliable positions of the nitro functional groups in the ligand through density functional theory.

[0065] In this invention, a 3H-2000PM2 specific surface area analyzer produced by Beijing Beishide Corporation was used to measure the specific surface area and pore volume of the porous coordination polymer. Before the test, the sample was subjected to vacuum degassing treatment at 373K, and the nitrogen adsorption-desorption isotherm curve was measured at 77K. The specific surface area and pore volume of the sample were analyzed by the BET method. Among them, micropores refer to pores with a pore diameter less than 2nm.

[0066] Micropore ratio % = (micropore volume / total pore volume) × 100%.

[0067] In this invention, an NH 3 -TPD experiment was carried out on the porous coordination polymer using an Autochem II 2920C chemisorption instrument produced by Micromeritics of the United States to measure its acidity and acid amount. During the measurement process, first, 0.2g of the sample was placed at 500°C and purged and activated with nitrogen at a flow rate of 30 mL / min, then cooled to 100°C to adsorb ammonia. After adsorption saturation, the temperature was raised to 700°C at a rate of 10°C / min for desorption, and detection was carried out through a TCD detector.

[0068] In this invention, a pyridine adsorption infrared spectroscopy experiment was carried out on the porous coordination polymer using an EQUINOX 55 infrared spectrometer produced by Bruker of Germany. The KBr tablet pressing method was used, and the scanning wave number range was from 4000 cm -1 to 400 cm -1 . First, the sample thin slice was vacuum purified at 450°C for 3h, then adsorbed pyridine vapor at room temperature for 30min, desorbed at 150°C for 1h, and the infrared spectrum was recorded to obtain the B acid and L acid amounts of the catalyst.

[0069] In this invention, a GC-2014C gas chromatograph produced by Shimadzu Corporation of Japan was used for product composition analysis. During the analysis process, a hydrogen flame ionization detector and an HP-5ms capillary column were used.

[0070] In this invention, the reaction temperature is 70°C, the reaction pressure is atmospheric pressure (i.e., 1 atm CO 2 ), using the porous coordination polymer as a catalyst, the mass ratio of epichlorohydrin, aqueous tetrabutylammonium bromide solution and the catalyst is 1:1.04:0.27, and the mass concentration of the aqueous tetrabutylammonium bromide solution is 10.5%. The reaction was completed in a glass reaction kettle, the stirring speed was 210 rpm. After the reaction was completed, the obtained mixture was analyzed by gas chromatography.

[0071] In this invention, the yield refers to the ratio of chloropropane carbonate to the raw material epichlorohydrin after the reaction, that is, the ratio of the product obtained after the reaction to the main raw material.

[0072] In this invention, except for pure CO 2In addition to the catalytic conditions, the catalytic test under the mixed gas conditions is as follows. The reaction temperature is 70 °C, and the reaction pressure is atmospheric pressure (i.e., 0.15 atm CO 2 / 0.73 atm N 2 / 0.05 atm H 2 O / 0.03 atm O 2 / 0.04 atm SO 2 ). Using a porous coordination polymer as the catalyst, the mass ratio of epichlorohydrin, aqueous tetrabutylammonium bromide solution, and the catalyst is 1:1.04:0.27, and the mass concentration of the aqueous tetrabutylammonium bromide solution is 10.5%. The reaction is completed in a glass reaction kettle, the stirring speed is 210 rpm. After the reaction is completed, the obtained mixture is analyzed by gas chromatography.

[0073] Example 1

[0074] Take the old PEN plastic and rinse it repeatedly with deionized water, dry it at 60 °C for 10 h, and use a crusher to make it into PEN powder with a mesh size of 130. Take 15 g of PEN powder and place it in 50 g of an aqueous sodium hydroxide solution with a mass concentration of 15%. After stirring at 450 rpm and 25 °C, it is loaded into a stainless-steel reaction kettle with a polytetrafluoroethylene liner and allowed to stand and react at 205 °C for 22 h. After the obtained product is cooled to 25 °C, 130 g of an aqueous oxalic acid solution with a mass concentration of 33% is added, and the mixture is stirred and reacted at 90 °C and 400 rpm for 3 h. The product is filtered by suction, washed with acetone, and dried at 120 °C for 13 h to obtain 2,6-naphthalenedicarboxylic acid. Weigh 20 g of 2,6-naphthalenedicarboxylic acid and dissolve it in 60 g of an aqueous hydrochloric acid solution with a mass concentration of 10%. At 0.5 °C and 12000 rpm, 15 g of a 17% nitroacetic acid solution is added dropwise at a rate of 1 g:1.24 mL / min. Subsequently, under reflux conditions, the solution temperature is raised to 63 °C at a heating rate of 2.8 °C / min and held at this temperature for 60 min, then raised to 105 °C and held at this temperature for 10 h. Subsequently, an ice-water mixture is added until the solution reaches 25 °C. The product is filtered by suction, washed with acetone, and dried at 85 °C for 21 h to obtain the ligand. Take 14 g of gallium nitrate nonahydrate and dissolve it in 1600 g of a mixed solvent of N,N-dimethylacetamide, acetonitrile, and deionized water with a mass ratio of 5:5:2. Ultrasonic treatment is carried out at a power of 40 kHz for 7.5 min, 4.8 g of the ligand is added, and ultrasonic treatment is carried out at a power of 115 kHz for 20 min. Then it is transferred to a stainless-steel reaction kettle with a polytetrafluoroethylene liner and allowed to stand and react at 105 °C for 25 h. The obtained product is washed with a 1:1 combination of N,N-dimethylformamide and anhydrous methanol, and vacuum dried at 160 °C for 12 h to obtain a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O8 Ga 2 n , where n is from 150 to 350.

[0075] Example 2

[0076] Take PEN plastic and rinse it repeatedly with deionized water. Dry it at 60 °C for 10 h, and use a pulverizer to make PEN powder with a mesh size of 130. Take 15 g of PEN powder and place it in 40.5 g of an aqueous sodium hydroxide solution with a mass concentration of 15%. Stir at 450 rpm and 25 °C, then load it into a stainless-steel reaction kettle with a polytetrafluoroethylene liner. Let it stand and react at 205 °C for 22 h. After the obtained product cools to 25 °C, add 102 g of an aqueous oxalic acid solution with a mass concentration of 33%. Stir and react at 90 °C and 400 rpm for 3 h. Filter the product by suction, wash it with acetone, and dry it at 120 °C for 13 h to obtain 2,6-naphthalenedicarboxylic acid. Weigh 20 g of 2,6-naphthalenedicarboxylic acid and dissolve it in 38 g of an aqueous hydrochloric acid solution with a mass concentration of 10%. At 0.5 °C and 12,000 rpm, add 12.6 g of a 17% nitroacetic acid solution dropwise at a rate of 1 g:1.24 mL / min. Then, under reflux conditions, raise the solution temperature to 63 °C at a heating rate of 2.8 °C / min and keep it at a constant temperature for 60 min. Raise the temperature to 105 °C again and keep it at a constant temperature for 10 h. Subsequently, add an ice-water mixture until the solution reaches 25 °C. Filter the product by suction, wash it with acetone, and dry it at 85 °C for 21 h to obtain the ligand. Take 14 g of gallium nitrate nonahydrate and dissolve it in 1428 g of a mixed solvent of N,N-dimethylacetamide, acetonitrile, and deionized water with a mass ratio of 5:5:2. Ultrasonically treat it at a power of 40 kHz for 7.5 min, add 4.34 g of the ligand, ultrasonically treat it at a power of 115 kHz for 20 min, transfer it to a stainless-steel reaction kettle with a polytetrafluoroethylene liner, let it stand and react at 105 °C for 25 h. Wash the obtained product with a combination of N,N-dimethylformamide and anhydrous methanol with a mass ratio of 1:1, and vacuum dry it at 160 °C for 12 h to obtain a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0077] Example 3

[0078] Compared with Example 1, the difference is that the pulverization fineness of the PEN powder is reduced to 60 mesh, and other reaction conditions and material compositions remain unchanged to obtain a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 ​​Ga 2 n , where n is from 150 to 350.

[0079] Example 4

[0080] Compared with Example 1, the difference is that the aqueous sodium hydroxide solution with a mass concentration of 15% is changed to an aqueous sodium hydroxide solution with a mass concentration of 25%, and other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0081] Example 5

[0082] Compared with Example 1, the difference is in the ligand preparation stage. Instead of standing and reacting at 205 °C for 22 h and waiting for the obtained product to cool to 25 °C, it is changed to standing and reacting at 150 °C for 35 h and waiting for the obtained product to cool to 25 °C. Other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0083] Example 6

[0084] Compared with Example 1, the difference is in the ligand preparation stage. Instead of adding 130 g of an aqueous oxalic acid solution with a mass concentration of 33%, 130 g of an aqueous malic acid solution with a mass concentration of 33% is added. Other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0085] Example 7

[0086] Compared with Example 1, the differences are that 15 g of PEN powder is placed in 15 g of an aqueous sodium hydroxide solution with a mass concentration of 15%, and also 225 g of an aqueous oxalic acid solution with a mass concentration of 33% is added. Other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N​​​​2 O 8 Ga 2 n , where n is from 150 to 350.

[0087] Example 8

[0088] Compared with Example 1, the difference is that instead of dissolving 20 g of 2,6-naphthalenedicarboxylic acid in 60 g of hydrochloric acid aqueous solution with a mass concentration of 10%, 20 g of 2,6-naphthalenedicarboxylic acid is dissolved in 60 g of hydrochloric acid aqueous solution with a mass concentration of 5%. Other reaction conditions and material compositions remain unchanged, and a porous coordination polymer is obtained. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0089] Example 9

[0090] Compared with Example 1, the difference is that the cooling environment temperature in "subsequently, under reflux conditions, the solution temperature is raised to 63 °C at a heating rate of 2.8 °C / min and kept constant for 60 min, then raised to 105 °C and kept constant for 10 h, and then ice-water mixture is added until the solution reaches 25 °C" is reduced to -15 °C. Other reaction conditions and material compositions remain unchanged, and a porous coordination polymer is obtained. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0091] Example 10

[0092] Compared with Example 1, the difference is that the stirring speed in "adding 15 g of nitroacetic acid with a mass concentration of 17% dropwise at a speed of 1 g:1.24 mL / min at 0.5 °C and 12000 rpm" is decreased to 8000 rpm. Other reaction conditions and material compositions remain unchanged, and a porous coordination polymer is obtained. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0093] Example 11

[0094] ​​​​Compared with Example 1, the difference is that 4-nitrocinnamic acid is used instead of nitroacetic acid, and other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0095] Example 12

[0096] Compared with Example 1, the difference is that the mass of the hydrochloric acid aqueous solution in "weighing 20 g of the ligand and dissolving it in 60 g of a 10% hydrochloric acid aqueous solution" is increased to 172 g, and the mass of nitroacetic acid is reduced to 5 g, while other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0097] Example 13

[0098] Compared with Example 1, the difference is that the dropping speed ratio in "dropping 15 g of a 17% nitroacetic acid at a speed of 1 g:1.24 mL / min" is increased to 1 g:3.5 mL / min, and other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0099] Example 14

[0100] Compared with Example 1, the difference is that the solution temperature under reflux conditions in "subsequently raising the solution temperature to 63 °C at a heating rate of 2.8 °C / min under reflux conditions and holding for 60 min" is raised to 90 °C, the heating rate is reduced to 1 °C / min, and the holding time is shortened to 10 min, while other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.​​​​

[0101] Example 15

[0102] Compared with Example 1, the difference is that the temperature for the second heating in "heating to 105 °C again and holding for 10 h, then adding ice - water mixture until the solution reaches 25 °C" is increased to 150 °C, and the holding time is shortened to 4 h, while other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0103] Example 16

[0104] Compared with Example 1, the difference is that in the process of preparing the nitro ligand, "washing with acetone and drying at 85 °C for 21 h to obtain the ligand", the washing solvent is replaced with deionized water instead of acetone, while other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0105] Example 17

[0106] Compared with Example 1, the difference is that gallium chloride hexahydrate is used instead of gallium nitrate nonahydrate, while other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0107] Example 18

[0108] Compared with Example 1, the difference is that a mixed solvent of anhydrous methanol and deionized water (mass ratio 5:2) is used instead of the mixed solvent of N,N - dimethylacetamide, acetonitrile and deionized water, while other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.​​​​

[0109] Example 19

[0110] Compared with Example 1, the difference is that the ultrasonic treatment power in "ultrasonic treatment for 7.5 min at a power of 40 kHz and adding 4.8 g of nitro ligand" is increased to 100 kHz and the time is shortened to 2 min, while other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is 150 - 350.

[0111] Example 20

[0112] Compared with Example 1, the difference is that the mass of the mixed solvent in "dissolving 14 g of gallium nitrate nonahydrate in 1600 g of a mixed solvent of N,N-dimethylacetamide, acetonitrile, and deionized water with a mass ratio of 5:5:2" is reduced to 1022 g, and the mass of the nitro ligand in "ultrasonic treatment for 7.5 min at a power of 40 kHz and adding 4.8 g of nitro ligand" is increased to 12.6 g, while other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is 150 - 350.

[0113] Example 21

[0114] Compared with Example 1, the difference is that the ultrasonic treatment power in "ultrasonic treatment for 20 min at a power of 115 kHz and transferring to a stainless steel reaction kettle with a polytetrafluoroethylene liner" is reduced to 50 kHz and the time is shortened to 5 min, while other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is 150 - 350.

[0115] Example 22

[0116] ​​​Compared with Example 1, the difference lies in the stage of preparing the porous coordination polymer. The static reaction temperature of "standing and reacting at 105°C for 25 h" is decreased to 55°C, and the time is extended to 36 h. Other reaction conditions and material compositions remain unchanged, and a porous coordination polymer is obtained. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0117] Example 23

[0118] Compared with Example 1, the difference lies in the stage of preparing the porous coordination polymer. Diethyl ether is used instead of the combination of N,N-dimethylformamide and anhydrous methanol as the organic solvent. Other reaction conditions and material compositions remain unchanged, and a porous coordination polymer is obtained. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0119] Example 24

[0120] Compared with Example 1, the difference lies in the stage of preparing the porous coordination polymer. The temperature of the vacuum drying treatment is decreased to 100°C, and the time is extended to 18 h. Other reaction conditions and material compositions remain unchanged, and a porous coordination polymer is obtained. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 150 to 350.

[0121] Comparative Example 1

[0122] Compared with Example 1, the difference lies in using 28% ammonia water by mass instead of the sodium hydroxide aqueous solution. Other reaction conditions and material compositions remain unchanged, and a porous coordination polymer is obtained. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is from 75 to 100.

[0123] Comparative Example 2

[0124] ​​​​Compared with Example 1, the difference lies in that an aqueous hydrochloric acid solution with a mass concentration of 10% is used instead of the aqueous oxalic acid solution, and other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is 60 - 100.

[0125] Comparative Example 3

[0126] Compared with Example 1, the difference lies in that during the preparation of the ligand, the 0.5 °C cooling environment in "adding 15 g of nitroacetic acid with a mass concentration of 17% dropwise at a rate of 1 g:1.24 mL / min at 0.5 °C and 12,000 rpm" is replaced with a 25 °C room temperature environment, and other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is 50 - 80.

[0127] Comparative Example 4

[0128] Compared with Example 1, the difference lies in that nitric acid is used instead of nitroacetic acid, and other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is 80 - 120.

[0129] Comparative Example 5

[0130] Compared with Example 1, the difference lies in that the process of raising the solution temperature to 63 °C at a heating rate of 2.8 °C / min is omitted, and the mixed solution containing nitroacetic acid is directly heated to quickly raise the temperature to 63 °C, and other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is 90 - 130.

[0131] Comparative Example 6

[0132] ​​​​Compared with Example 1, the difference is that the process of reheating is omitted, that is, the process of "reheating to 105 °C and maintaining a constant temperature for 10 h" is not carried out, and other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is 90 to 130.

[0133] Comparative Example 7

[0134] Compared with Example 1, the difference is that copper nitrate trihydrate is used instead of gallium nitrate nonahydrate, and other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer with copper as the ionic center.

[0135] Comparative Example 8

[0136] Compared with Example 1, the difference is that chloroform is used instead of the mixed solvent of N,N-dimethylacetamide, acetonitrile and deionized water, and other reaction conditions and material compositions remain unchanged, obtaining a porous coordination polymer. The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , where n is 70 to 120.

[0137] Comparative Example 9

[0138] According to the method described in CN116622085A, 5 g of aluminum nitrate nonahydrate was added to 35 mL of DMF and 15 mL of deionized water, stirred until completely dissolved, and then the mixed solution was transferred to a hydrothermal reaction kettle, 2.5 g of PET powder was added, mixed evenly, and heated and reacted at 180 °C for 48 h to obtain Product 1; Product 1 was washed three times with 90 mL of DMF, centrifuged, and the precipitate was retained to obtain Product 2; Product 2 was washed three times with 90 mL of absolute ethanol and centrifuged to obtain Product 3; Product 3 was first dried at 80 °C for 12 h and then dried at 110 °C for 12 h to obtain the metal-organic framework material MIL-53(Al).

[0139] Comparative Example 10

[0140] According to the method described in CN110283353A, a 0.5 mol / L sodium acetate buffer solution was prepared, 5 mL was taken and placed in a reaction kettle, and then a polyacid precursor substance (0.15 g of Na 9 (PW 9 O 34 ), 0.4 g of NiCl 2 ·6H​​2 O), and then add waste polyester plastic fragments (PET), stir evenly, heat the reaction kettle to 180 °C and maintain it for 72 h. After it cools to room temperature, select and separate the unreacted PET, and obtain the polyacid-based metal-organic framework material (Ni-POMOF) through filtration, washing, and drying.

[0141] Test Example 1

[0142] Determine the physical and chemical properties of the porous polymers in Examples 1-24 and Comparative Examples 1-11. The specific results are shown in Table 1.

[0143] Table 1 Properties of the porous polymers prepared in Examples and Comparative Examples

[0144]

[0145]

[0146] As can be seen from Table 1, the porous coordination polymers prepared in the present invention have good physical and chemical properties. The nitrogen and gallium contents of the sample in Example 1 reach 3.5% and 5.5% respectively, and its specific surface area, microporosity, and average pore diameter are 1460 m 2 / g, 85%, and 0.85 nm respectively, and the medium-strong acid amount and L / B value reach 0.75 mmol / g and 1.42 mmol / g respectively. The corresponding parameters of the comparative example samples are significantly lower than those of the example samples. From Figure 1 and Figure 2 SEM photos, it can be seen that the porous coordination polymer sample prepared in Example 1 has a regular morphology structure and well-developed capillary pores, which is helpful for catalytic reactions, while the morphology of the sample in Comparative Example 1 is irregular and the pore structure in the surface structure is not clear enough.

[0147] Test Example 2

[0148] Determine the effects of preparing chloropropane carbonate and the product composition in the cycloaddition reaction of epichlorohydrin and carbon dioxide in Examples 1, 7, Comparative Example 4, and Comparative Example 7. The specific results are shown in Tables 2 and 3.

[0149] Table 2 Effects of the reaction of preparing chloropropane carbonate in the cycloaddition reaction of epichlorohydrin and carbon dioxide under single-gas conditions in Examples and Comparative Examples

[0150] Catalyst sample Conversion rate of epichlorohydrin / % Selectivity of chloropropane carbonate / % Yield of chloropropane carbonate / % Example 1 99.8 99.8 98.7 Example 7 99.5 99.3 97.9 Comparative Example 4 67.5 76.4 57.9 Comparative Example 7 60.8 71.3 50.6

[0151] Table 3 Effects of the reaction of preparing chloropropane carbonate in the cycloaddition reaction of epichlorohydrin and carbon dioxide under mixed-gas conditions in Examples and Comparative Examples

[0152] Catalyst sample Conversion rate of epichlorohydrin / % Selectivity of chloropropane carbonate / % Yield of chloropropane carbonate / % Example 1 95.7 98.9 90.4 Example 7 94.1 98.2 88.3 Comparative Example 4 67.5 76.4 57.9 Comparative Example 7 60.8 71.3 50.6

[0153] As can be seen from Table 2 and Table 3, the porous coordination polymer prepared by the method of the present invention has good effects in the synthesis of chloropropane carbonate in the cycloaddition reaction of epichlorohydrin and carbon dioxide, as well as high yields and selectivities of chloropropane carbonate. Under single gas conditions, the conversion rate of epichlorohydrin, the selectivity of chloropropane carbonate, and the yield of chloropropane carbonate of the sample in Example 1 were 99.8%, 99.8%, and 98.7% respectively, while the corresponding reaction results of the sample in the comparative example were all lower than those of the sample in the example. Under mixed gas conditions, the conversion rate of epichlorohydrin, the selectivity of chloropropane carbonate, and the yield of chloropropane carbonate of the sample in Example 1 were 95.7%, 98.9%, and 90.4% respectively, still maintaining a high reaction effect.

[0154] The present invention has been described in detail above in combination with specific embodiments and examples, but these descriptions should not be construed as limiting the present invention. Those skilled in the art understand that without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements can be made to the technical solutions of the present invention and their implementation manners, and all of these fall within the scope of the present invention. The protection scope of the present invention shall be subject to the appended claims.

Claims

1. A porous coordination polymer, wherein, The molecular formula of the porous coordination polymer is [C 12 H 4 N 2 O 8 Ga 2 n , and the monomer of its structural formula is as follows:​ wherein n is 150 to 350.

2. The porous coordination polymer according to claim 1, characterized in that the mass content of gallium in the porous coordination polymer is 3% to 6%.

3. The porous coordination polymer according to claim 1 or 2, characterized in that in the porous coordination polymer, the mass content of carbon is 53% to 62%, the mass content of oxygen is 21% to 33%, and the mass content of nitrogen is 2.3% to 3.7%.

4. The porous coordination polymer according to claim 1, characterized in that the porous coordination polymer has an inner helical structure.

5. The porous coordination polymer according to claim 1, characterized in that The specific surface area of the described porous coordination polymer is 1280 m 2 / g to 1460 m 2 / g, the microporosity is 75% to 85%, and the average pore diameter is 0.68 nm to 0.85 nm; and / or, the total acid amount of the porous coordination polymer is 1.35 mmol / g to 1.56 mmol / g, the medium-strong acid amount is 0.63 mmol / g to 0.75 mmol / g, and the ratio of the amount of L acid to the amount of B acid (L / B) is 1.31 to 1.

42.

6. A method for preparing the porous coordination polymer according to any one of claims 1-5, comprising the following steps: (1) Synthesize the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid; (2) Dissolve the gallium salt in a mixed solvent, add the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid described in step (1), and react to obtain the porous coordination polymer.

7. The preparation method according to claim 6, characterized in that the synthesis method of the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid in step (1) is to obtain the ligand by nitrating 2,6-naphthalenedicarboxylic acid. Preferably, 2,6-naphthalenedicarboxylic acid is first purified from waste PEN plastic, and then the ligand is obtained by nitrating 2,6-naphthalenedicarboxylic acid.

8. The preparation method according to claim 7, characterized in that the method for synthesizing the ligand 4,8-dinitro-2,6-naphthalenedicarboxylic acid in step (1) specifically comprises the following steps: (i) Take the waste PEN plastic, crush it, place it in an alkali solution for a first reaction, and then add an acid solution for a second reaction, wash and dry to obtain 2,6-naphthalenedicarboxylic acid; (ii) Dissolve the 2,6-naphthalenedicarboxylic acid in step (i) in acid solution A, and then dropwise add it to acid solution B for nitration reaction to obtain 4,8-dinitro-2,6-naphthalenedicarboxylic acid.

9. The preparation method according to claim 8, characterized in that the mass ratio of the waste PEN plastic to the alkali solution in step (i) is 1:(1 to 10); and / or, the first reaction in step (i) is a static reaction, wherein the first reaction temperature is 150°C to 250°C and the time is 10 h to 35 h; and / or, the acid solution in step (i) is selected from one or more of oxalic acid aqueous solution, citric acid aqueous solution, and malic acid aqueous solution, and the mass concentration of the acid solution is 28% to 36%; and / or, the mass ratio of the PEN plastic to the acid solution in step (i) is 1:(4 to 15).

10. The preparation method according to claim 8, characterized in that The acid solution A described in step (ii) is selected from aqueous hydrochloric acid solutions, with a mass concentration of 5% to 20%; and / or, the mass ratio of the 2,6-naphthalenedicarboxylic acid to the acid solution A described in step (ii) is 1:(0.8 - 8.6); and / or, the acid solution B described in step (ii) is selected from one or more of nitroacetic acid, aqua regia, and 4-nitrocinnamic acid; and / or, the mass ratio of the 2,6-naphthalenedicarboxylic acid to the acid solution B described in step (ii) is 1:(0.25 - 2.35); and / or, the ratio of the mass of the 2,6-naphthalenedicarboxylic acid to the dropping rate of the acid solution B in step (ii) is 1 g:(0.75 mL / min - 3.5 mL / min).

11. According to the preparation method described in claim 8, characterized in that in step (ii), the addition of the acid solution B is carried out under a cooling ambient temperature with stirring, where the cooling ambient temperature is -15°C to 6°C; and / or, the heating reaction in step (ii) undergoes a two-stage heating reaction. In the first stage, the solution temperature is programmed to rise to the first reaction temperature under reflux conditions and then held at a constant temperature; the first reaction temperature is 30°C to 90°C, the heating rate is 1°C / min to 10°C / min, and the constant temperature time is 10 min to 100 min; in the second stage, the temperature is further raised to the second reaction temperature of 50°C to 160°C, and the constant temperature time is 4 h to 20 h; where the second reaction temperature is at least 30°C higher than the first reaction temperature.

12. According to the preparation method described in claim 6, characterized in that in step (2), the gallium salt is selected from one or more of gallium nitrate nonahydrate, gallium chloride hexahydrate, and gallium sulfate; and / or, the mixed solvent described in step (2) is at least one organic solvent selected from N,N-dimethylformamide, acetonitrile, anhydrous methanol, N,N-dimethylacetamide, and diethyl ether and water, and the mass ratio of the organic solvent to water is (1.4 - 2.5):(0.08 - 0.85); and / or, in step (2), the mass ratio of the gallium salt, the mixed solvent, and the ligand is 1:(73 - 156):(0.21 - 0.96).

13. Application of the porous coordination polymer described in any one of claims 1 - 5 as a catalyst in the preparation of chloropropane carbonate by the cycloaddition reaction of epichlorohydrin and carbon dioxide.

14. According to the application described in claim 13, characterized in that in the said reaction, an aqueous solution of tetrabutylammonium bromide is added as a reaction assistant, and the mass ratio of epichlorohydrin, the aqueous solution of tetrabutylammonium bromide, and the catalyst is 1:(0.65 - 1.17):(0.16 - 0.34); wherein, the mass concentration of the aqueous solution of tetrabutylammonium bromide is 7.3% to 13.6%; And / or, the carbon dioxide is pure carbon dioxide or a mixed gas containing carbon dioxide. In the mixed gas, the volume percentage of CO 2 is 10% to 20%.

15. According to the application described in claim 13, characterized in that the reaction conditions are: the reaction temperature is 50°C to 80°C, the reaction pressure is atmospheric pressure, and the reaction time is 30 h to 60 h.

Citation Information

Patent Citations

  • Method for preparing metal-organic frameworks by one-step degradation of polyacid-induced waste polyester plastics

    CN110283353A

  • Metal organic framework material prepared on basis of waste PET (polyethylene terephthalate) as well as preparation method and application of metal organic framework material

    CN116622085A